Analisis Terhadap Perjanjian Waralaba (Franchise) Usaha Toko Alfa Mart - Tami Rusli (KEADILAN PROGRESIF, 2015)
Franchise is defined as the privilege that exists and or supplied by the franchisor to the franchisee with a payment obligation. In franchising there are obligations and rights should exist, then made an agreement in this franchise arrangement, which was later renamed the franchise agreement. Relating to the franchise agreement Alfa Mart then the problem is, How will the franchise agreement on a mini retail outlet at Alfa Mart in order to provide legal protection for the parties to make an agreement. The survey results revealed that the franchise agreement arrangements made to provide legal protection for each party involved in the franchise agreement. Suggestions are expected to Government as soon as possible to make the Law on wararalaba that Act can better ensure the rights of the parties involved in the franchise agreement.